UJI AKTIVITAS ANTIOKSIDAN KOMBINASI SEDUHAN TEH HERBAL DAUN KEJI BELING (Strobilanthes crispus L.) DAN KAYU MANIS (Cinnamomum burmannii) DENGAN VARIASI SUHU PENYEDUHAN - Egata, Neisa; Hilma, Hilma; Rasyad, Ade Arinia; Sirumapea, Lasmaryna; Munarsih, Ensiwi; Hasanah, Mauizatul; Romsiah, Romsiah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Herbal tea has many health benefits. Herbal tea has attracted public attention as a potential source of natural antioxidants. Keji Beling leaves (Strobilanthes crispus L.) and cinnamon bark (Cinnamomum burmannii) are natural ingredients that can be processed into herbal tea that has antioxidant compounds. The purpose of this study was to determine the antioxidant activity value (IC50) of the combination of Keji Beling tea and cinnamon (1:0, 0:1, and 1:1) with variations in brewing temperatures of 60°C and 80°C for 5 minutes. Antioxidant testing used the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The results of this study indicate that a 1:1 comparison sample at 60°C can have greater antioxidant activity than the two single sample with an IC50 value of 60.13 ppm.Keywords: Antioxidant, keji beling, cinnamon, infusion, herbal tea.